Evaluating the toxicity of sea-dumped conventional and chemical munition degradation products to fish and human cells using a combination of cell viability assays - João Barbosa; Colin R. Janssen; Marijke Neyts; Koen Parmentier; Frédéric Laduron; Kris Geukens; Philippe François; Jana Asselman (Ecotoxicology and Environmental Safety)
The disposal of munitions in marine coastal areas after World Wars I and II has raised significant concerns about environmental contamination and human health risks. This study investigates the acute cytotoxicity of munition-related chemicals commonly detected near marine dumpsites, focusing on degradation products of explosives and related compounds (E&RC) and degradation products of chemical warfare agents and related compounds (CWA&RC). The research examines three CWA&RC (1,4-oxathiane, 1,4-dithiane, thiodiglycol) and four E&RC (2,4,6-trinitrotoluene, tetryl, 1,3-dinitrobenzene, picric acid) using the RTgill-W1 cell line (rainbow trout gill cells) as a proxy for fish toxicity and human cell lines (Caco2 and HepG2) to model potential human exposure via contaminated seafood. The results indicate low acute cytotoxicity of CWA&RC, while E&RC exhibit significantly higher toxicity. Notably, the EC10 and EC50 values for tetryl and 1,3-DNB in RTgill-W1 align with concentrations detected near North American dumpsites, reflecting environmentally relevant conditions. The study also reveals inter-species and inter-organ variability in toxicity mechanisms, identifying potential adverse outcome pathways such as AOP 220. These findings highlight the need for further research into chronic exposure scenarios at environmentally realistic concentrations and contribute crucial data to understanding the risks posed by the degradation products of these chemicals to aquatic life and human health.